Influência de parâmetros físicos e geométricos na estimativa do módulo de deslizamento em ligações de estruturas mistas de madeira e concreto - Politi, Maria Julia (2024)
The composite structures of timber and concrete appeared at the end of the First and Second World Wars, with the intention of replacing steel. This system seeks to use the advantages of both materials, wood presents good performance in tension and concrete in compression, however, due to the different properties of the materials it is difficult to predict the exact working mechanism of the connection system, thus how to measure the calculation of the slip modulus. In this scenario, the present research aimed to evaluate the factors that influence the service slip modulus (Kser) in a T-section beam composed of a concrete table and a wooden core, joined by metallic connectors. This analysis was carried out using a parametric approach via the finite element method, so that in the end it was possible to obtain a multiple variable regression equation to estimate the Kser with coefficient of determination R2 = 79.07 %, which highlights the good precision obtained in estimating this important structural variable.